Application of the UTAUT Model for Acceptance Analysis of COBIT Implementation in E-Learning Management with Microsoft Teams on Distance Learning in Batam City - Suwarno Suwarno (Khazanah Informatika, 2022)
Since March 2020, due to the COVID-19 pandemic and in line with Merdeka Belajar - Kampus Merdeka, higher education institutions have conducted distance learning in asynchronous and synchronous modes, such as video meetings using Microsoft Teams and provide e-learning. In order to reach the goals and strategies of the higher education institutions, universities implement several control objectives within the COBIT 5 framework, so they can use and manage resources efficiently, provide the best education for students. This study aims to analyze the acceptance level of the COBIT implementation in higher education institutions by using the UTAUT model in E-Learning management, the use of Microsoft Teams and distance learning. This study uses a quantitative approach with a causal explanatory research design. Dissemination of the survey was conducted by simple random sampling at 6 (six) universities in Batam City. This study reveals that E-Learning management, the use of Microsoft Teams, and the application of distance learning together have a significant influence on the implementation of COBIT with an acceptance index of 85.5%, which refers to the satisfying category.